Association of rodent-borne Leptospira spp. with urban environments in Malaysian Borneo - Blassdell, Kim R.; Morand, Serge; David, Perera; Firth, Cadhla (PLOS, 2019)
Although leptospirosis is traditionally considered a disease of rural, agricultural and flooded environments, Leptospira spp. are found in a range of habitats and infect numerous host species, with rodents among the most significant reservoirs and vectors. To explore the local ecology of Leptospira spp. in a city experiencing rapid urbanization, we assessed Leptospira prevalence in rodents from three locations in Malaysian Borneo with differing levels of anthropogenic influence: 1) high but stable influence (urban); 2) moderate yet increasing (developing); and 3) low (rural). A total of 116 urban, 122 developing and 78 rural rodents were sampled, with the majority of individuals assigned to either the Rattus rattus lineage R3 (n = 165) or Sundamys muelleri (n = 100). Leptospira spp. DNA was detected in 31.6% of all rodents, with more urban rodents positive (44.8%), than developing (32.0%) or rural rodents (28.1%), and these differences were statistically significant. The majority of positive samples were identified by sequence comparison to belong to known human pathogens L. interrogans (n = 57) and L. borgpetersenii (n = 38). Statistical analyses revealed that both Leptospira species occurred more commonly at sites with higher anthropogenic influence, particularly those with a combination of commercial and residential activity, while L. interrogans infection was also associated with low forest cover, and L. borgpetersenii was more likely to be identified at sites without natural bodies of water. This study suggests that some features associated with urbanization may promote the circulation of Leptospira spp., resulting in a potential public health risk in cities that may be substantially underestimated.